Valorization of Palm Empty Fruit Bunch-Derived K₂CO₃ Catalyst: Structural Analysis and Application in Biodiesel Production - Arita, Susila; Fitriyanti, Reno; Komariah, Leily Nurul; Hadiah, Fitri (Science and Technology Indonesia, 2026)
This study investigates the synthesis and performance of a K2CO3 catalyst derived from oil palm empty fruit bunch (EFB) ash for sustainable biodiesel production. X-ray Diffraction (XRD) revealed a dominant K2CO3 crystalline phase, while X-ray Fluorescence (XRF) confirmed a high potassium content (>40%). Despite its low surface area (0.11 m2/g), the catalyst demonstrated high transesterification activity, achieving an optimal biodiesel yield of 85.89% with 3 grams of catalyst. Its high thermal stability, strong base sites, and macroporous structure all contributed to enhanced catalytic efficiency. Sustainability and techno-economic assessments indicate the catalyst’s potential to reduce production costs, utilize biomass waste, and lower greenhouse gas emissions. Thus, the EFB ash-based K2CO3 catalyst shows significant promise for supporting environmentally friendly biodiesel production and contributing to the transition to a green economy and renewable energy.